"A strong desire to get into the bands": Small Group Formation in 1740s British Methodism - Watson, Kevin M. (Wesley and Methodist studies, 2021)
This article considers thirteen manuscript letters from the Early Methodist Volume, a valuable collection of letters housed at the John Rylands Research Institute and Library, University of Manchester. The thirteen letters range from 19 May 1740 to June 1742. These manuscript letters give insight into lay Methodism, revealing conflict in the beginnings of the Evangelical Revival, developments in small group formation (especially the band meeting), pastoral care within the bands, and the pursuit of holiness in community in the early 1740s. This article shows the significance of the band meeting among Methodists connected to Charles Wesley in these crucial years.